Thermal modelling of single and double slope passive solar stills for different climatic zones in India. Issue 1 (31st December 2022) - Akshay, Chetpelly; Soni, Palash; Dhiman, Sushil Kumar; Bhowmick, Shubhankar; Gaba, Vivek Kumar
Abstract : Thermal modelling of Single Slope Passive Solar Still (SSSS) and Double Slope Passive Solar Still (DSSS) has been carried out for different climatic zones in India and a MATLAB code has been developed to analyse solar radiation and yield which were validated for yield output with benchmark results. Temperature variations on hourly basis at glass cover and basin water, heat transfer coefficients and yield were evaluated. For maximum yield output based on latitude angle, the yield variation of SSSS and DSSS for six cities of India from different climatic zones was compared. It is observed that the corresponding percentage increase in yields of DSSS over SSSS for cities, such as Chennai, Goa, Jaipur, Mumbai, New Delhi and Raipur, are 91.3%, 89.3%, 70.92%, 93.25%, 56.88% and 75.87% for a summer day and 63.37%, 57.91%, 55.59%, 44.30%, 6.15% and 34.29% for a winter day, respectively.